2021
DOI: 10.1007/s11934-021-01079-1
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Clinical Benefit for Peri-operative Administration of Tranexamic Acid for Patients Undergoing Percutaneous Nephrolithotomy? A Systematic Review and Meta-analysis

Abstract: Purpose of ReviewThe purpose of current systematic review and meta-analysis is to determine the efficacy and safety of the administration of tranexamic acid in patients undergoing PCNL. The study was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement. This systematic review and meta-analysis includes randomized comparative prospective studies. Recent Findings The primary endpoints were the hemoglobin drop, the bleeding complications, and the transfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Several systematic reviews [22,24,[47][48][49][50][51] have focused on the use of TXA in the PCNL setting, but most have serious methodological limitations and none to date has rated the CoE on a per-outcome basis. Multiple reviews [47][48][49][50][51] found TXA may reduce hospital length of stay GRADE Working Group grades of evidence: 'High certainty': we are very confident that the true effect lies close to that of the estimate of the effect. 'Moderate certainty': we are moderately confident in the effect estimate: the true effect is likely to be close to the estimate of the effect, but there is a possibility that it is substantially different.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several systematic reviews [22,24,[47][48][49][50][51] have focused on the use of TXA in the PCNL setting, but most have serious methodological limitations and none to date has rated the CoE on a per-outcome basis. Multiple reviews [47][48][49][50][51] found TXA may reduce hospital length of stay GRADE Working Group grades of evidence: 'High certainty': we are very confident that the true effect lies close to that of the estimate of the effect. 'Moderate certainty': we are moderately confident in the effect estimate: the true effect is likely to be close to the estimate of the effect, but there is a possibility that it is substantially different.…”
Section: Discussionmentioning
confidence: 99%
“…Two reviews [22,50] use the outdated Jadad system for addressing study quality. Three of these studies utilised a registered protocol [47,48,51] whereas the others did not. Importantly, TEE were not considered as an outcome of interest in three reviews [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another feared complication of PCNL is bleeding, regardless of tract size, with the CROES study reporting an overall bleeding risk of 7.8% [12]. Tranexamic acid has gained immense popularity of the 2 years with multiple studies showing a decrease in bleeding and increase in stone-free rate [13–16,17 ▪▪ ,18]. Batagello et al [17 ▪▪ ] published a randomized, double-blinded, placebo-controlled trial assessing a single-dose of tranexamic acid in patients undergoing PCNL.…”
Section: Bleedingmentioning
confidence: 99%